2019
DOI: 10.7773/cm.v45i3.2969
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the Mexican barracuda, Sphyraena ensis Jordan and Gilbert, 1882, in the southeastern end of the Gulf of California

Abstract: Understanding the feeding habits of the Mexican barracuda, Sphyraena ensis Jordan and Gilbert, 1882, is important to elucidate relevant aspects of its trophic ecology (prey intake, diet breadth, trophic level, and energy flows), which in general provide valuable information on the dynamics of marine communities. Therefore, the purpose of this work was to assess the dietary habits of the Mexican barracuda, S. ensis, and to determine dietary variations by sex (males, females), size (small, medium, and large indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our study shows that ectoparasites (monogenean, copepod) have a higher dominance in S. ensis than endoparasites. As the route of infestation of gastrointestinal endoparasites is closely associated to the host's diet (Poulin, 1995), it can be expected that opportunistic predatory fish that feed mainly on bony fish and zoobenthos, such as S. ensis (López-Peralta and Arcila, 2002;Moreno-Sánchez et al, 2019) are parasitized by a greater quantity and diversity of endoparasites. However, based on the collected samples of S. ensis parasites, these data come from the coast of Peru and additionally in the information in the literature (table 5), this does not occur in S. ensis because of the species of parasites reported for this fish; only two species are endoparasitic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study shows that ectoparasites (monogenean, copepod) have a higher dominance in S. ensis than endoparasites. As the route of infestation of gastrointestinal endoparasites is closely associated to the host's diet (Poulin, 1995), it can be expected that opportunistic predatory fish that feed mainly on bony fish and zoobenthos, such as S. ensis (López-Peralta and Arcila, 2002;Moreno-Sánchez et al, 2019) are parasitized by a greater quantity and diversity of endoparasites. However, based on the collected samples of S. ensis parasites, these data come from the coast of Peru and additionally in the information in the literature (table 5), this does not occur in S. ensis because of the species of parasites reported for this fish; only two species are endoparasitic.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into account, it is to be expected that S. ensis, a predatory fish and opportunistic ichthyophage, which feeds mainly on bony fish that form schools such as Sardinops spp. (40.36 %), Hemiramphus saltator (40.24 %), and also zoobenthos (López-Peralta and Arcila, 2002;Moreno-Sánchez et al, 2019) would be parasitized by a high number and diversity of endoparasites. Moreno-Sánchez et al (2019) found no differences between the diet and the TBL and the sex of S. ensis.…”
Section: Site Of Parasites Taxa Infection Location Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Studies on food and feeding aspects of some barracuda species have been conducted globally; these species include S. jello and S. obtusata from Arabian Sea (Premalatha & Manojkumar, 1990); S. guachancho from the eastern Atlantic Ocean (Akadje et al, 2013); S. viridensis from Azores (Barreiros et al, 2002); S. jello from Persian Gulf (Hosseini et al, 2009); S. chrysotaenia and S. flavicauda from the Gulf of Suez (Osman et al, 2019); S. viridensis, S. sphyraena and S. chrysotaenia from Rhodes Island (Kalogirou et al, 2012); S. ensis from the southern shelf of Colombia and south-eastern Gulf of California (Lopez-Peralta & Arcila, 2002;Moreno-Sanchez et al, 2019); S. barracuda off Colombia (Hooker et al, 2007); and S. sphyraena from Cape Coast (Aggrey-Fynn et al, 2013). Most barracudas, except S. flavicauda, are specialized piscivores, with finfishes constituting 70% to close to 100% of the prey species.…”
Section: Introductionmentioning
confidence: 99%